2018
DOI: 10.3389/feduc.2018.00103
|View full text |Cite
|
Sign up to set email alerts
|

Activists, Non-activists, and Allies: Civic Engagement and Student Types at MSIs

Abstract: Higher education institutions across the country aim to contribute to students' ability to become active citizens. Civic engagement has long been an emphasis of higher education and has become a focal point from innovations such as the Carnegie Foundation's elective classification for community engagement and service-learning (Saltmarsh and Zlotkowski, 2011). Researchers have demonstrated that foundational values of democratic engagement including inclusiveness, relationships between students who engaged in cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Critical action involves social and political behaviors enacted to resist oppression and promote social justice for marginalized communities (Aldana et al., 2019; Diemer et al., 2016). For Black college students, critical action can include participating in Black cultural organizations, mainstream student government, or hosting educational forums to spread awareness about a social issue, particularly in the face of racial discrimination (Fassett et al., 2018; Harper & Quaye, 2007). Critical action plays an important role for Black students who must navigate racial challenges with peers and faculty (Cerezo et al., 2014; Petchauer, 2011).…”
Section: Overview Of Conceptual Frameworkmentioning
confidence: 99%
“…Critical action involves social and political behaviors enacted to resist oppression and promote social justice for marginalized communities (Aldana et al., 2019; Diemer et al., 2016). For Black college students, critical action can include participating in Black cultural organizations, mainstream student government, or hosting educational forums to spread awareness about a social issue, particularly in the face of racial discrimination (Fassett et al., 2018; Harper & Quaye, 2007). Critical action plays an important role for Black students who must navigate racial challenges with peers and faculty (Cerezo et al., 2014; Petchauer, 2011).…”
Section: Overview Of Conceptual Frameworkmentioning
confidence: 99%
“…In research practice, Mezirow argued that transformative learning challenges students to assess their value system and worldview and to be potentially changed by the experience [42,43]. Moreover, civic engagement is embedded in the history of minority student groups on campuses with their influence on increased access and capacity to inform themselves or others about an issue [44].…”
Section: Studies On Civic Engagement and Transferabilitymentioning
confidence: 99%
“…For instance, signing a petition or making a social media post can be done quickly on a smartphone or computer. While, on average, participants engaged in some form of activism nearly once a week and thus, were similarly engaged in political activities as compared to other college student samples (e.g., Fassett et al, 2018;Hope et al, 2016), students reported engagement in higher-accessibility forms of activism much more frequently than resource mobilization or collective action types of activism. Notably, this category of high-accessibility activism is not one that has been well-studied in the activism literature and our findings may speak to a cluster of behaviors that have increasingly become accessible as a function of the ease of access to technology (e.g., smartphones) and growing usage of social media over the past decade.…”
Section: Feeling Personally Affected As a Moderatormentioning
confidence: 81%